2017
DOI: 10.1016/j.energy.2016.12.080
|View full text |Cite
|
Sign up to set email alerts
|

Heating and cooling energy trends and drivers in Europe

Abstract: This paper aims to complete and complement the information available on the past trends of thermal energy consumption in residential buildings and its drivers for Europe, as a continent and for the different countries. This paper follows the drivers identified in a previous one for the heating and cooling energy consumption, decomposing this energy demand into key drivers based on a Kaya identity approach: number of households, persons per household, floor space per capita and specific energy consumption for r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
36
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(37 citation statements)
references
References 14 publications
1
36
0
Order By: Relevance
“…Regarding climate mitigation in the building sector, earlier studies have shown the contribution of energy-saving technologies (e.g. high-efficient air conditioners and thermal insulation (Serrano et al 2017, Waite et al 2017a, Hanaoka et al 2014. The contribution of human behavioral change to energy demand, such as refraining from excessive use of air conditioners, has also been assessed (Fujimori et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding climate mitigation in the building sector, earlier studies have shown the contribution of energy-saving technologies (e.g. high-efficient air conditioners and thermal insulation (Serrano et al 2017, Waite et al 2017a, Hanaoka et al 2014. The contribution of human behavioral change to energy demand, such as refraining from excessive use of air conditioners, has also been assessed (Fujimori et al 2014a).…”
Section: Introductionmentioning
confidence: 99%
“…2019, 9, 1104 2 of 34 are nowadays available and many more practical and multi-disciplinary research projects are under development. When considering only the energy requirements for the heating and cooling in residential and commercial buildings, it is already a third of the total global use and, more importantly, it should increase by approximatively 79% and 84% between 2010 and 2050 [1,2].To overcome the use of heating and cooling devices, the use of phase change materials (PCM) has been proposed. They can authorize to benefit from free heating or cooling or to delay the thermal stress, to name but a few examples for passive applications.…”
mentioning
confidence: 99%
“…2019, 9, 1104 2 of 34 are nowadays available and many more practical and multi-disciplinary research projects are under development. When considering only the energy requirements for the heating and cooling in residential and commercial buildings, it is already a third of the total global use and, more importantly, it should increase by approximatively 79% and 84% between 2010 and 2050 [1,2].…”
mentioning
confidence: 99%
“…Underfloor and ceiling heating show a similar behaviour, with operative temperatures approaching, and often exceeding, the air temperature. Analytical and numerical calculations have an 1 We will show that the t op obtained this way is not radically different from the analytical result. excellent agreement and show a maximum t op for sizes smaller than the whole width of the room.…”
Section: Introductionmentioning
confidence: 74%
“…The energy performance of heating emitters is a key factor in the energy demand of the building sector, which is primarily determined by space heating [1][2][3]. Such devices can be of very different type (panel radiators, convectors, ceiling and underfloor heating...), each determining the energy demand in a specific way [4][5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%